2021
DOI: 10.3389/fimmu.2021.715036
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Eculizumab for Treating Myasthenia Gravis

Abstract: Myasthenia gravis (MG) is an autoimmune disease primarily mediated by acetylcholine receptor antibodies (AChR-Ab), cellular immune dependence, and complement system involvement. Since the AChR on the postsynaptic membrane is destroyed by an immune attack, sufficient endplate potential cannot be generated, resulting in the development of a synaptic transmission disorder at the neuromuscular junction and in muscle weakness. The role of the complement system in MG has been demonstrated in animal models and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Physiologically, several molecules, including decay-accelerating factor (CD55) and C1 esterase inhibitor, act to prevent inappropriate complement activation directed towards self cells. 12,13 The Role of Complement in MG Preclinical Data…”
Section: Cellular Recruitment (Figure 2c)mentioning
confidence: 99%
“…Physiologically, several molecules, including decay-accelerating factor (CD55) and C1 esterase inhibitor, act to prevent inappropriate complement activation directed towards self cells. 12,13 The Role of Complement in MG Preclinical Data…”
Section: Cellular Recruitment (Figure 2c)mentioning
confidence: 99%
“…44 Eculizumab does not have any role in reducing antibody production and acts only on the complement cascade. 45 The risk of meningococcaemia is another potential problem with eculizumab, and patients receiving this drug should be vaccinated against Neisseria meningitidis 2 weeks prior to starting eculizumab. 46 The beneficial effects of eculizumab compared with placebo led to its approval by the FDA for its use in refractory, AChR antibody-positive MG. 47 An open-label extension of the REGAIN trial also demonstrated a significant reduction in rates of exacerbation of MG, rates of MG-related hospitalization and increase in global clinical improvement scores.…”
Section: Touchreviews In Neurologymentioning
confidence: 99%
“…Other side effects reported include diarrhea, upper respiratory infection, and arthritis. Notably, no cases of meningococcal infection were reported, possibly due to vaccination prior to enrollment in the study [6]. The therapies administered to patients at the beginning of eculizumab administration were IVIg, prednisone, pyridostigmine, mycophenolate, and azathioprine.…”
Section: Eculizumabmentioning
confidence: 99%
“…Additionally, eculizumab seemed to present a favorable benefit-risk profile in pregnant patients and no adverse reactions in either the patient or the infant. Notably, a few patients were recruited, and the findings should be considered cautiously [6,7].…”
Section: Eculizumabmentioning
confidence: 99%